Prediction Method of Residual Subsidence of Strip Goaf Located in Suburb for Safely Constructing Viaduct - Chao Tang; Huaizhan Li; Guangli Guo; Yaqiang Gong; Xuewei Zhang; Cheng Huang; Huaan Zhou; Yafei Yuan; Wenqi Huo; Guangli Dai; Chao Liu (Energy Exploration & Exploitation, 2024)
Resource-based cities often face land scarcity during their developmental and expansionary phases. However, repurposing the goaf sites of suburban coal mines has been recognized as an effective strategy for alleviating this issue, particularly pertinent for suburban coal mines using strip mining techniques to protect ground-level structures. Old strip mining goaf is easily influenced by disturbance and leads to secondary surface deformation, which will threaten the construction above old strip mining goaf. Therefore, it is essential to provide a basis and reference for decision-makers regarding surface residual subsidence for strip mining. In the paper, based on the morphology and structure of the old strip mining goaf before the surface residual subsidence, the reason and mechanism of the residual subsidence of old strip mining goaf are studied. The results show that the main reasons for the “activation” of old strip mining goaf are the re-compaction of the under-compacted part of the fractured rock mass in the caving zone, the stripping and yielding of coal pillar under the action of groundwater erosion, weathering, and the collapse of residual voids. Based on the above analysis, a prediction model of the surface residual subsidence of the old strip mining goaf is proposed, which takes into account the compaction of the under-compacted area, the collapse of the residual voids, and the stripping and yielding of the coal pillar. The proposed method is implemented to evaluate the stability of a city viaduct goaf. Our research outcomes bear valuable theoretical and practical implications for site stability assessments of old strip mining goafs and the sustainable repurposing of land resources in suburban resource-based cities.